2018
DOI: 10.1007/s00268-018-4752-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Retention and Decay of Basic Surgical Skills: Evidence from Addis Ababa University, Ethiopia: A Prospective Case–Control Cohort Study

Abstract: While our surgical skills course is an effective means to teach surgical skills to medical students, there is significant decay in abilities after 6 months. Conducting regular assessments does not appear to have any effect in helping students retain these skills. We recommend such surgical skills training be conducted at appropriate intervals, such as just before internship, to prepare student for active surgical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Paradoxically, evidence shows that skill decay begins from day 1 after the intervention (53)(54)(55). Moreover, from the studies investigating skill decay in our SR, four concluded that there was decay in the skills of students after the end of the teaching intervention (14,17,18,37). One of these studies concluded that although single instructional sessions improved suturing performance in the short-term (56), they were not sufficient to maintain suturing proficiency over longer periods of time (14).…”
Section: Student Participants As Indicated Inmentioning
confidence: 97%
See 4 more Smart Citations
“…Paradoxically, evidence shows that skill decay begins from day 1 after the intervention (53)(54)(55). Moreover, from the studies investigating skill decay in our SR, four concluded that there was decay in the skills of students after the end of the teaching intervention (14,17,18,37). One of these studies concluded that although single instructional sessions improved suturing performance in the short-term (56), they were not sufficient to maintain suturing proficiency over longer periods of time (14).…”
Section: Student Participants As Indicated Inmentioning
confidence: 97%
“…Only eight studies investigated the retention of skill acquisition after an extended time period (14, 17-19, 22, 31, 37, 38). Half of the studies concluded that there was decay in the skills of students after the end of the teaching intervention (14,17,18,37). Four studies evaluated skill retention at 30 days (14,17,19,22) and two at 7 days (18,31).…”
Section: Performance and Retention Of Suturing Skillsmentioning
confidence: 99%
See 3 more Smart Citations